Chinese public opinions on death penalty: measurement, analysis and communication. (2nd January 2020) - Liang, Genlin; Chen, Eryan
ABSTRACT: The preservation or the abolition of death penalty is an issue of public policy choice justified by public recognition. Policy decisions and system designs of death penalty should take public opinions seriously. Using data from more than 30, 000 samples, this research finds that the concept of retribution and deterrence constitutes the most important conceptual foundation for death penalty, upon which the majority of Chinese people are in favor of preservation of death penalty. However, the mainstream view towards death penalty has significantly changed, which suggests that the majority of Chinese people are not absolute retentionists, but either unconditional or conditional abolitionists. When appropriate alternative measures to death penalty are posed, nearly 80% retentionists will turn into abolitionists. Public opinions of death penalty are influenced by a variety of factors including self-actualization, dependence of mass media, social unfair experiences, sense of security, legal awareness as well as evaluation of social problems. The discourse pattern is the most suitable pattern for China to lead public opinions towards a rational direction. According to this pattern, it is advisable to promote all-round development of human beings as well as civilization and harmony of the society, value the crucial role of political elites, establish appropriate alternative measures to death penalty and communicate with the public through mass media, so as to lay solid socio-psychological foundation for the gradual reform of death penalty in China.